Identification of a Novel FAM83H Mutation and Management of Hypocalcified Amelogenesis Imperfecta in Early Childhood - Ji-Soo Song; Yejin Lee; Teo Jeon Shin; Hong-Keun Hyun; Young-Jae Kim; Jung-Wook Kim (Children, 2022)
Amelogenesis imperfecta (AI) is a heterogeneous group of rare genetic disorders affecting amelogenesis during dental development. Therefore, the molecular genetic etiology of AI can provide information about the nature and progress of the disease. To confirm the genetic etiology of AI in a Korean family with an autosomal dominant inheritance, pedigree and mutational analyses were performed. DNA was isolated from the participating family members and whole-exome sequencing was performed with the DNA sample of the father of the proband. The identified mutation was confirmed by Sanger sequencing. The mutational analysis revealed a novel nonsense mutation in the FAM83H gene (NM_198488.5: c.1363C > T, p.(Gln455*)), confirming autosomal dominant hypocalcified AI. Full-mouth restorative treatments of the affected children were performed after the completion of the deciduous dentition. Early diagnosis of AI can be useful for understanding the nature of the disease and for managing the condition and treatment planning.